2019
DOI: 10.1055/s-0039-1683925
|View full text |Cite
|
Sign up to set email alerts
|

Higher Function Scores and Satisfaction in Patients with Anteromedial Osteoarthritis Compared with Other Wear Patterns of the Knee: 2 Years after Both Total and Unicondylar Knee Arthroplasties

Abstract: Anteromedial osteoarthritis (AMOA) is a common wear pattern in primary osteoarthritic knees. In patients with bone-on-bone disease, the most appropriate surgical intervention is still a matter of debate. Knee arthroplasty is a well-accepted treatment to relieve symptoms and regain function. Unfortunately, satisfaction is limited, especially related to activities. A cross-sectional study was performed among patients treated with total knee arthroplasty (TKA) and unicondylar arthroplasty (UKA) to determine if th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…After screening the titles and abstracts, 44 related studies were first screened out. After conducting a full-text review on the remaining studies, 13 studies were left in the final analysis, including 4 RCTs and 9 non-RCTs (cohort and case-control studies) [3,5,9,12,13,[23][24][25][26][27][28][29][30].…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening the titles and abstracts, 44 related studies were first screened out. After conducting a full-text review on the remaining studies, 13 studies were left in the final analysis, including 4 RCTs and 9 non-RCTs (cohort and case-control studies) [3,5,9,12,13,[23][24][25][26][27][28][29][30].…”
Section: Study Selectionmentioning
confidence: 99%
“…UKR accounts for only 9% of all knee replacements in the UK [3]. On the contrary, TKR is a widely accepted, reliable, cost-effective and suitable surgical method for patients with end-stage OA targeting at pain reduction, function restoration and improvement of healthrelated life quality [9,10]. Despite these positive effects, 17-19% of patients were dissatisfied after TKR [11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have evaluated differences in objective functional outcome scores (Knee Society Score or HSS score) and most studies have reported comparable outcomes [ 11 , 13 15 ]. Only a few studies have reported patient-reported outcomes (PROMs) [ 16 18 ]. To the best of our knowledge, there is only one study published, that objectively compares patellofemoral symptoms, reporting the incidence of anterior knee pain and the Anterior Knee Pain Score (AKPS), after either procedure [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have reported patient-reported outcomes (PROMs) [ 16 18 ]. To the best of our knowledge, there is only one study published, that objectively compares patellofemoral symptoms, reporting the incidence of anterior knee pain and the Anterior Knee Pain Score (AKPS), after either procedure [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It accounts for about half of all patients with knee osteoarthritis. However, at present, for some patients with medial compartment, whether it is suitable for direct total knee arthroplasty, there are still objections at home and abroad [13][14][15]. For this reason, as early as the late 1960s, some scholars had proposed a surgical treatment for single compartment osteoarthritis of the knee joint, which was called single condylar replacement [16].…”
Section: Introductionmentioning
confidence: 99%